The Effect of Hydrostatic Pressure and Cationic Vacancy on the Electronic and Magnetic Properties of the ZnSe:T Crystals (T = Ti, V, Cr, Mn, Fe, Co, Ni) - Syrotyuk, Stepan (East European Journal of Physics, 2021)
The parameters of the spin-polarized electronic energy spectrum of ZnSe:T crystals (T = Ti, V, Cr, Mn, Fe, Co, Ni) are studied on the basis of a 2 × 2 × 2 supercell built on the basis of a ZnSe unit cell with a sphalerite structure. The supercell contains 64 atoms, with one Zn atom replaced by one transition 3d element T. The first stage of this study is to calculate in the ideal material ZnTSe parameters of electronic energy bands, dependent on the external hydrostatic pressure. At the second stage, the effect of pressure on the parameters of the electronic energy spectrum in the ZnTSe materials is investigated, taking into account the Zn vacancy. The calculations were performed using the Abinit program. For a better description of strongly correlated 3d electrons of the element T, a hybrid exchange-correlation functional PBE0 with an admixture of the Hartree-Fock exchange potential was used, in which the self-interaction error of these electrons is removed. Based on the obtained spin-polarized electron densities of states, the magnetic moments of the supercells were also determined. A significant effect of pressure on the parameters of electronic energy zones was revealed. So, the ideal ZnTiSe material at zero pressure is a metal for both spin values, but under pressure it becomes a semiconductor. The same material with a point defect, i.e. a vacancy at the site of the Zn atom, exhibits semiconductor properties for both spin orientations at zero pressure. It was found that vacancies radically change the parameters of electronic energy bands. The magnetic moments of the supercell, as integral values of the spin-polarized densities of electronic states, also reflect these changes. Thus, in ZnTiSe material without defects, the magnetic moments of the supercell are 1.92, 2.0 and 2.0, at pressures 0, 21 and 50 GPa, respectively, while in the same material with a vacancy, the corresponding values are 0.39, 0.02 and 0.36. The ideal ZnVSe material at zero pressure is also a metal for both values of the spin moment, but in the presence of a cationic vacancy it is characterized by a pseudogap because the Fermi level is localized in the upper part of the valence band. Ideal ZnFeSe and ZnNiSe crystals are characterized by similar dependences of the electronic energy parameters on the pressure, for both spins. However, the same materials with a cationic vacancy are characterized by the Fermi level immersed in the valence band for a spin up.